Pengaruh Manjemen Risiko Perusahaan, Ukuran Perusahaan, dan Leverage terhadap Kinerja Keuangan di Masa Pandemi Covid-19 - Nabila Salsabila; Risal Rinofah; Pristin Prima Sari (Ekonomis: Journal of Economics and Business, 2023)
This study aims to examine and understand the effect of CAR, NPL, company size, and leverage on financial performance in the form of ROA of banks listed on the IDX for the 2018-2020 period. The population used in this study were 47 banks listed on the IDX. The type of data used in this research is secondary data. The sampling technique used purposive sampling and obtained a sample of 41 people. Collecting data in this study using the documentation method. The analytical method used is descriptive statistical test, classical assumption test, multiple linear regression, hypothesis testing, different test. So the results of the study show that CAR, NPL, leverage have a negative and insignificant effect on financial performance, firm size has a positive and significant effect on financial performance, and CAR, NPL, firm size, and leverage have a simultaneous effect on financial performance. . Whereas before and during the company size CAR, ROA and NPL, and leverage there was no difference before or during Covid-19.